Study on Initial Management of Sepsis in Tertiary Care Centre: A Prospective Study - Biyyala, Susmitha (International Journal of Pharmaceutical & Biological Archive, 2022)
Background: Sepsis and septic shock are the major health problems affecting millions of people around the world each year and the incidence is as many as 1 in 4. According to Centers for Disease Control and Prevention the incidence of sepsis continues to increase and is now the 3rd leading cause of infectious death. In India, sepsis claims more than 90,000 lives every year and is one of the leading causes of death. Early effective management of sepsis as per Surviving sepsis Campaign guidelines can improve the patient outcomes, prevent further complications, and decrease the mortality. Aim: Our study aims to evaluate the Initial Management of Sepsis in an Institution and identify the areas of improvement. Methods: It is a prospective observational study conducted in a tertiary care center. A structured data collection form was designed to collect the information from medical records of the patients. Sepsis investigation details such as source of infection, blood, and urine cultures were collected. Additional information such as initial antibiotic started, door to first antibiotic, fluids used, and other supportive care (Deep vein thrombosis and Stress ulcer prophylaxis) was collected, assessed, and reviewed for the initial 2 days. Results: A total of 100 cases were collected. Number of patients diagnosed with sepsis and septic shock was found to be (78%) and (22%), respectively. Males (55%) were more affected compared to females (45%). Diabetes with hypertension and hypothyroidism (40%) was the common comorbid observed. Common source of infections were found to be lower respiratory tract infection (41%) followed by urinary tract infections (19%). Majority of the patients received appropriate Antibiotics within 1 h as per guidelines. A Sequential Organ Failure Assessment score of >3 was found in 26%. Fluid therapy was given to 78% of the patients. Vasoactive medications were given to all patients with septic shock (22%). Conclusion: In our hospital setting, the overall adherence to guidelines was found to be optimal and satisfactory. However, there is need for improvement in some areas.